Clinico-anatomical correlations in uncomplicated stroke. Issue 11 (November 1984) - Allen, C M; Hoare, R D; Fowler, C J; Harrison, M J
Abstract : A method for making clinico-anatomical correlations by computer superimposition of brain maps derived from CT scan images, described in a companion paper, was tested in 19 patients with an uncomplicated left hemiparesis due to acute stroke. Eight patients with an isolated left hemiparesis had small lesions in the most rostral part of the right internal capsule. The composite lesion maps of 11 patients whose left hemiparesis was complicated only by spinothalamic sensory loss showed a larger area of damage more caudally in the posterior part of the posterior limb of the capsule, abutting the thalamus. The close correlation between the results obtained by this method and those obtained in previous clinico-pathological studies of patients with uncomplicated strokes, confirms the validity of this mapping technique.